2018
DOI: 10.1208/s12248-018-0267-9
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle-Based Delivery of CRISPR/Cas9 Genome-Editing Therapeutics

Abstract: The recent progress in harnessing the efficient and precise method of DNA editing provided by CRISPR/Cas9 is one of the most promising major advances in the field of gene therapy. However, the development of safe and optimally efficient delivery systems for CRISPR/Cas9 elements capable of achieving specific targeting of gene therapy to the location of interest without off-target effects is a primary challenge for clinical therapeutics. Nanoparticles (NPs) provide a promising means to meet such challenges. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
64
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(64 citation statements)
references
References 178 publications
0
64
0
Order By: Relevance
“…After endocytosis, internalized material is found in endosomes (pH 6.5–6.8), which develop to be late endosomes (pH 5.2–6.0), before moving into lysosomes (pH 4.5–5.2) where it is subjected to degradation by enzymes and the acidic environment ( Figure 4 B) [ 155 ]. Endosomal escape is considered to be the bottleneck in the development of most non-viral vectors, including CPPs, with very low endosomal escape efficiencies [ 155 , 156 ].…”
Section: Mechanism Of Cpp-uptake and Releasementioning
confidence: 99%
See 1 more Smart Citation
“…After endocytosis, internalized material is found in endosomes (pH 6.5–6.8), which develop to be late endosomes (pH 5.2–6.0), before moving into lysosomes (pH 4.5–5.2) where it is subjected to degradation by enzymes and the acidic environment ( Figure 4 B) [ 155 ]. Endosomal escape is considered to be the bottleneck in the development of most non-viral vectors, including CPPs, with very low endosomal escape efficiencies [ 155 , 156 ].…”
Section: Mechanism Of Cpp-uptake and Releasementioning
confidence: 99%
“…After endocytosis, internalized material is found in endosomes (pH 6.5–6.8), which develop to be late endosomes (pH 5.2–6.0), before moving into lysosomes (pH 4.5–5.2) where it is subjected to degradation by enzymes and the acidic environment ( Figure 4 B) [ 155 ]. Endosomal escape is considered to be the bottleneck in the development of most non-viral vectors, including CPPs, with very low endosomal escape efficiencies [ 155 , 156 ]. This has been reported, in many studies employing CPPs to deliver plasmids, proteins or siRNA, as punctate distribution of the internalized CPPs, suggesting that they are remaining within endosomal vesicles [ 157 , 158 , 159 ].…”
Section: Mechanism Of Cpp-uptake and Releasementioning
confidence: 99%
“…Gene editing methods that are highly efficient like CRISPR or ZFNs are delivered via viral vectors and by interrupting CCR5, the CCR5 co-receptors become unavailable to HIV virus. CRISPR-Cas9 mediated systems that are delivered via non-viral vectors have also been developed including liposome like lipid based reagents (Cardarelli, et al 2016), polymer polyethyleneimine (PEI) and nanoparticle based (Givens, et al 2018) systems. However, since non-viral methods have lower efficiency, studies on improving the efficiency of the delivery have been done such as in a study where mouse models were being studied.…”
Section: Where Crispr-cas9 Falls Shortmentioning
confidence: 99%
“…For generating less cytotoxic side effects many novel nanoparticle investigations are being done for carrying CRISPR-Cas9 mediated systems into cells. When formulated differently, nanoparticles might have predilections for different tissues and organs such as liposome based ones being more preferable for lungs while different particles will be more suited for liver (Givens, et al 2018).…”
Section: Can Akpinaroglu / Gene Editingmentioning
confidence: 99%
“…[10] Additionally, it has been reported that up to 70% of patients could have pre-existing immunity to AAV, which may limit it's efficacy as a therapy. [15] Depending on the type of material used, nanocarriers have the ability to carry different types of cargo and can be chemically modified for colloidal stability, biodegradability, biocompatibility, and tissue specificity. [12] This sustained expression of bacterially derived Cas9 has the potential to enhance off-target activity or to prompt an immune response against Cas9 and the muscle.…”
mentioning
confidence: 99%